RANCANG BANGUN SISTEM TELEMETRI UNTUK MONITORING GAS LPG DENGAN MENGGUNAKAN JARINGAN Wi – Fi - Satryo Adi Wibowo; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
This research is abaout the telemetry system for monitoring LPG gas concentration using a Wi-Fi network. This research is driven by a need to carry out monitoring of a distant object whose data can be received in real-time and continuously transmitted by the transmitter of the sensor used. The telemetry system is built with ATMega 8535 microcontroller to read analog data from the sensor and converted to digital data. For LPG gas concentration measurement using LPG gas sensor MQ-5, utilizing the RS-232 protocol as serial data communication and Wi-Fi networks as an intermediary for the transmission of information. Use Wi-Fi network for data transmission is an option that is appropriate, given the use of Wi-Fi increasingly popular among the people. LPG gas sensor has an analog output and therefore takes the ADC to convert analog data into digital data that can be read in mikrokontroler The data that has been read by the microcontroller sent using RS232 protocol, then the serial data is stored into the database in a microprocessor. The interface created with php and html language to display data LPG gas concentration from the microprocessor at the point of monitoring. Web browser used on the PC server by entering the IP address adrress of microprocessor that stores the database. Wi-Fi networks are used as transfer media databases of the microprocessor in the PC server to the monitoring point at the observation point. Results of the comparison between the data transmitted and received data has error = 0 so certainly no data is lost or gained. Keywords: LPG gas, telemetry, sensor, serial communications, database.